Conserving tropical biodiversity via strategic spatiotemporal harvest planning. Issue 6 (9th August 2013) - Ramage, Benjamin S.; Marshalek, Elaina C.; Kitzes, Justin; Potts, Matthew D.; Rhodes, Jonathan
Summary Tropical timber production forests have the potential to harbour many species, but landscape‐level management strategies for minimizing extinctions are lacking. To develop relevant conservation guidelines, we investigated how harvest plans with different spatiotemporal patterns affected the persistence of sessile species with different traits and preharvest characteristics. We confronted this problem via an individual‐based simulation model. We explored several harvest plans with different levels of spatiotemporal aggregation, but equivalent total harvest area, and found that extinction probabilities for each plan varied with species traits and predisturbance characteristics. Most notably, plans with large contiguous harvest units yielded particularly high extinction probabilities for dispersal‐limited habitat specialists with clustered preharvest distributions. Differences between plans were small for some types of species, but highly aggregated plans yielded the highest extinction rates for all extinction‐prone groups. Synthesis and applications. Our simulations suggest that reducing the size of contiguous harvest units, even while total harvest area remains constant, may reduce extinction rates in tropical production forests (assuming that road‐related threats can be effectively managed). Our findings have important implications for tropical conservation efforts and also provide general insight into the compositional effects of disturbances with different spatiotemporal characteristics.